IoTEventSim: an Event-Driven Simulator for Large-Scale IoT Applications in Cloud–Fog–Edge Architectures - Coelho, Paulo; Silva, Abadio de Paulo; Pasquini, Rafael; Miani, Rodrigo; Sens, Pierre; Arantes, Luciana (Anais do Workshop de Testes e Tolerância a Falhas (WTF); 2026: Anais do XXVII Workshop de Testes e Tolerância a Falhas, 2026)
Large-scale Internet of Things (IoT) applications increasingly span cloud–fog–edge infrastructures, where application behavior depends on dynamic network conditions, mobility, and device energy constraints. Evaluating such systems in real deployments is costly and difficult to reproduce, motivating simulation approaches that must balance realism and scalability. This paper presents IoTEventSim, an event-driven simulator designed for per-device modeling and runtime control in distributed IoT scenarios. In IoTEventSim, each device is modeled as an autonomous entity with explicit communication, battery, and location parameters, while transient and permanent events dynamically modify device behavior over time. The simulator natively supports MQTT and CoAP and provides a web-based interface for scenario management and monitoring. We evaluate IoTEventSim in geo-distributed cloud–fog–edge settings parameterized from FIT IoT-LAB measurements. Results show that the simulator reproduces the target latency and drop characteristics with high fidelity and scales to thousands of concurrently monitored devices without saturating CPU or network resources in the evaluated environment. These findings indicate that IoTEventSim is a practical environment for controlled, repeatable performance, robustness, and fault-experimentation studies of IoT applications under adverse and time-varying conditions.